Synthesis of exchange coupled nanoflowers for efficient magnetic hyperthermia - Shaw S.K.; Biswas A.; Gangwar A.; Maiti P.; Prajapat C.L.; Meena S.S.; Prasad N.K. (My University, 2025)
Magnetic materials with high specific loss power (SLP) are desirable for magnetic hyperthermia to minimise the amount of material required to obtain the therapeutic temperature (42–46 °C) to destroy the cancer cells. The exchange coupled core-shell structure and the nanoclusters of magnetic nanoparticles having high SLP values are the most suitable candidates for this purpose. Herein, a simple method has been demonstrated for the synthesis of exchange coupled magnetic nanoflowers consisting of γ-Fe2O3 magnetic grains grown over the surface of MnFe2O4 core. The aqueous ferrofluid of nanoflowers displayed higher SLP values than single phase MnFe2O4 core. The intrinsic loss parameter for the nanoflowers was 3.30 nH m2 Kg−1 at an applied magnetic field of amplitude 250 Oe and frequency 113 kHz, which was significantly higher than the commercially available ferrofluids. The cytotoxicity of the nanoflowers were studied with HeLa cells. The magnetic hyperthermia treatment for 30 min with 0.75 mg/mL ferrofluid of the nanoflowers demonstrated a temperature rise to 46 °C and decreased the cell viability to 17% for HeLa cells. These nanoflowers (size around 40–60 nm) showed better magnetic properties viz. higher saturation magnetisation, initial susceptibility and lower coercivity, making them a suitable candidate for biomedical applications. © 2019 Elsevier B.V.